2017
DOI: 10.2147/nss.s125992
|View full text |Cite
|
Sign up to set email alerts
|

Infant sleep and its relation with cognition and growth: a narrative review

Abstract: ObjectiveInfant sleep development is a highly dynamic process occurring in parallel to and in interaction with cognitive and physical growth. This narrative review aims to summarize and discuss recent literature and provide an overview of the relation between infant sleep and cognitive development as well as physical growth.MethodsWe conducted online literature search using MEDLINE, Embase, and Cochrane Library databases. We considered original research on humans published in the English language from January … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
92
0
9

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 114 publications
(102 citation statements)
references
References 83 publications
(117 reference statements)
1
92
0
9
Order By: Relevance
“…Bell, Wagner, Feldman, Shypailo, and Belfort () reported that the body weight z score is higher in the first postnatal month for breastfed infants compared to those fed with baby formula. Some researchers have determined that infants who sleep less are shorter and have greater body mass index z scores and higher obesity rates compared to infants who sleep more (Nedeltcheva, Kessler, Imperial, & Penev, ; Tham, Schneider, & Broekman, ; Zhou et al, ). In our study, growth parameters (weight and head circumference z scores) of the babies in the intervention group, the mothers of who received web‐based education on baby care, sleep, and communication with the baby, were higher compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…Bell, Wagner, Feldman, Shypailo, and Belfort () reported that the body weight z score is higher in the first postnatal month for breastfed infants compared to those fed with baby formula. Some researchers have determined that infants who sleep less are shorter and have greater body mass index z scores and higher obesity rates compared to infants who sleep more (Nedeltcheva, Kessler, Imperial, & Penev, ; Tham, Schneider, & Broekman, ; Zhou et al, ). In our study, growth parameters (weight and head circumference z scores) of the babies in the intervention group, the mothers of who received web‐based education on baby care, sleep, and communication with the baby, were higher compared to the control group.…”
Section: Discussionmentioning
confidence: 99%
“…As has been identified elsewhere , many studies of infant sleep are based solely on parental reports (Field, 2017;Tham et al, 2017) captured via surveys or standardised questionnaires (Goh et al, 2017;Hughes et al, 2015;Sadeh et al, 2009;Symon and Crichton, 2017), sleep logs or diaries (Hiscock and Wake, 2002;Price et al, 2014), or recently, via smartphone apps (Mindell et al, 2016). The use of these methods assumes two things: a) that parents are able to accurately report on their infant's sleep, even though they may be asleep during much of what they are reporting on; and b) that even if parental reports are inaccurate, they will vary homogeneously and with consistency across families and thus discrepancies will have no systematic effect on outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…While previous studies have focused on the association of circadian rhythms with obesity and other medical conditions, few have studied the association between circadian rhythms and normal physical growth. 10,11 Details in the development and consolidation of circadian rhythms during early childhood remain to be studied and how circadian rhythms relate to early childhood development shall be investigated further. 5,10,11 This study aims to characterize the consolidation of sleep-wake rhythms during early childhood and further study its association with physical development.…”
Section: Introductionmentioning
confidence: 99%
“…10,11 Details in the development and consolidation of circadian rhythms during early childhood remain to be studied and how circadian rhythms relate to early childhood development shall be investigated further. 5,10,11 This study aims to characterize the consolidation of sleep-wake rhythms during early childhood and further study its association with physical development. The sleep-wake circadian rhythm is an important aspect of circadian studies, and sleep logs, polysomnography (PSG), and actigraphy are often used in such studies.…”
Section: Introductionmentioning
confidence: 99%